2020
DOI: 10.1002/dta.2865
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of legal and illegal Cannabis spp. according to European legislation using near infrared spectroscopy and chemometrics

Abstract: Aerial parts containing cannabidiol can be purchased in a legal way but cannabis used as recreational drug is illegal in most European countries. Δ9‐tetrahydrocannabinol is one of the main cannabinoids responsible for the psychotropic effect. European Union countries and Switzerland authorize a concentration of THC of 0.2 % and 1.0 % w/w, respectively, for smoking products and industrial hemp. Public health inspectors and law enforcement officers need to check the legality of samples. Therefore there is a need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Raman measurements, however, require direct contact of samples with the spectrometer to obtain high-quality signals (Sanchez et al, 2020). Duchateau et al (2020) used near-infrared spectroscopy for discriminating legal and illegal hemp, defined by a cut-off concentration of 0.2% THC in European Union countries, obtaining classification accuracies of 91-95%. Crushing dried hemp plants was required prior to the spectroscopic measurements (Duchateau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman measurements, however, require direct contact of samples with the spectrometer to obtain high-quality signals (Sanchez et al, 2020). Duchateau et al (2020) used near-infrared spectroscopy for discriminating legal and illegal hemp, defined by a cut-off concentration of 0.2% THC in European Union countries, obtaining classification accuracies of 91-95%. Crushing dried hemp plants was required prior to the spectroscopic measurements (Duchateau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Duchateau et al (2020) used near-infrared spectroscopy for discriminating legal and illegal hemp, defined by a cut-off concentration of 0.2% THC in European Union countries, obtaining classification accuracies of 91-95%. Crushing dried hemp plants was required prior to the spectroscopic measurements (Duchateau et al, 2020). Cirrincione et al (2021) reported on using attenuated total reflectance infrared spectroscopy for the discrimination between fiber-type and drug-type cannabis samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the application of NIR spectroscopy to cannabis analysis, only a few works can be found in the literature, showing some interesting applications [19][20][21][22]. In a recent work, the possibility of differentiating between legal and illegal cannabis inflorescences by using a qualitative model implemented with a handheld system was explored.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative data generated by NIR strongly agree with UHPLC-UV data, confirming the potential of employment of NIR spectroscopy in routine monitoring of cannabis plant material and cannabis resins [ 189 ]. Dispersive NIR and FT-NIR methods were developed for quantification of eight different phytocannabinoids (CBDV, Δ 9 -THCV, CBD, CBC, Δ 8 -THC, Δ 9 -THC, CBG and CBN) in ground leaves and inflorescences from C. sativa [ 205 ] and for discriminating illegal and legal cannabis varieties [ 207 ]. A similar NIR method demonstrated sensitivity and specificity for CBD quantification in different liquid pharmaceutical products, thus showcasing its potential as a fast method for monitoring of CBD in the production process [ 206 ].…”
Section: Analytical Methods For Phytocannabinoid Profilingmentioning
confidence: 99%